Transition to timber plantation based forestry in Indonesia: towards a feasible new policy - Obidzinski, K.; Chaudhury, M. (2009)
Indonesia’s forestry sector is in a dilemma due to the long-standing disparity between high processing capacity of forest industries and the limited supply of timber. The supply crunch has led to over-harvesting in order to meet demand and resulted in a decline of natural forests. The Indonesian government seeks to revive the forestry sector and secure its long term survival through a massive timber plantation effort: 9 million hectares of new plantations by 2016. This paper shows that while timber plantations are vital for the future of Indonesia’s woodworking sector, the expansion plan relies on overly optimistic assumptions about the current state of Indonesia’s timber plantations, their future performance, and associated benefi ts. In order to ensure effective implementation of the new plantation policy, this paper analyzes its key underlying principles and identifi es information gaps that need to be fi lled.